Promoting physical activity-related health competence to increase leisure-time physical activity and health-related quality of life in German private sector office workers - Blaschke, Simon; Carl, Johannes; Pelster, Klaus; Mess, Filip (BMC Public Health, 2023)
Background Office workers (OWs) are at risk of low levels of health-enhancing physical activity (HEPA) and impaired health-related quality of life (HRQOL). Interventions based on physical activity-related health competence (PAHCO) aim to facilitate long-term changes in HEPA and HRQOL. However, these assumptions rely on the changeability and temporal stability of PAHCO and have not been tested empirically. This study therefore aims to test the changeability and temporal stability of PAHCO in OWs within an interventional design and to examine the effect of PAHCO on leisure-time PA and HRQOL. Methods Three hundred twenty-eight OWs (34% female, 50.4 ± 6.4 years) completed an in-person, three-week workplace health promotion program (WHPP) focusing on PAHCO and HEPA. The primary outcome of PAHCO as well as the secondary outcomes of leisure-time PA and HRQOL were examined at four measurement points over the course of 18 months in a pre-post design by employing linear mixed model regressions. Results PAHCO displayed a substantial increase from the baseline to the time point after completion of the WHPP (β = 0.44, p < 0.001). Furthermore, there was no decrease in PAHCO at the first (p = 0.14) and the second follow-up measurement (p = 0.56) compared with the level at the end of the WHPP. In addition, the PAHCO subscale of PA-specific self-regulation (PASR) had a small to moderate, positive effect on leisure-time PA (β = 0.18, p < 0.001) and HRQOL (β = 0.26, p < 0.001). The subscale of control competence for physical training (CCPT) also had a positive small to moderate effect on HRQOL (β = 0.22, p < 0.001). Conclusion The results substantiate PAHCO’s theoretical characteristics of changeability and temporal stability, and underline the theoretically postulated effects on leisure-time PA and HRQOL. These findings highlight the potential of PAHCO for intervention development, which can be assumed to foster long-term improvements in HEPA and HRQOL in OW
Keywords: Health literacy; Physical literacy; Office workers; Health-related quality of life; Office workers; Behavioural change; Workplace health promotion